Obstetrics and perinatal outcomes of dichorionic twin pregnancy following ART compared with spontaneous pregnancy - Leila Pourali; Sedigheh Ayati; Shahrzad Jelodar; Ahmadreza Zarifian; Mohammad Sobhan Sheikh Andalibi (Iranian Journal of Reproductive Medicine, 2016)
Introduction: Regarding to the recent advances in assisted reproductive techniques (ART), twin and multiple pregnancies have increased during past years. Objective: This study was performed to compare obstetrics and perinatal outcomes of dichorionic twin pregnancy following ART with spontaneous pregnancy. Materials and Methods: In this cross-sectional study which was performed in Ghaem Hospital, Mashhad University of Medical Sciences, 107 dichorionic twin pregnancy were enrolled in two groups: spontaneous group (n=96) and ART group (n=31). Basic criteria and obstetrics and neonatal outcomes information including demographic data, gestational age, mode of delivery, pregnancy complications (preeclampsia, gestational diabetes, preterm labor, and intrauterine growth retardation (IUGR), postpartum hemorrhage), neonatal outcomes (weight, first and fifth minuteP PApgar score, Neonatal Intensive Care Unit (NICU) admission, mortality, respiratory distress, and icterus) were recorded using a questionnaire. Results: Preterm labor, gestational diabetes, and preeclampsia were significantly higher in ART group compared to spontaneous pregnancy group. However, other factors such as anemia, IUGR, postpartum hemorrhage, and intrauterine fetal death (IUFD) were not significantly different between groups. There were no significant differences between groups in terms of neonatal outcomes (weight, 1PstP and 5PthP min Apgar score <7, NICU hospitalization, mortality, respiratory distress, and icterus). Conclusion: With regard of significantly higher poor outcomes such as preeclampsia, gestational diabetes and preterm labor in ART group, the couples should be aware of these potential risks before choosing ART.